Inorganic copolymer anticorrosive paint and preparation method thereof

Through the synergistic effect of modified nano-titanium dioxide and modified epoxy resin with zinc phosphate and aluminum tripolyphosphate, combined with silica sol and kaolin to form an inorganic network structure, the problems of insufficient film-forming property and flexibility of inorganic anti-corrosion coatings are solved, high corrosion resistance and environmental protection are achieved, and it is suitable for high-end industrial fields.

CN120795667AActive Publication Date: 2025-10-17IANGSU JINLING SPECIAL PAINT CO LTD

Patent Information

Application Number
CN202511258015.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-04
Publication Date
2025-10-17
Estimated Expiration
2045-09-04

AI Technical Summary

Technical Problem

Existing inorganic anti-corrosion coatings have poor film-forming properties, insufficient flexibility, easy cracking, and unstable coatings. In addition, traditional preparation processes make it difficult to ensure sufficient reaction of each component, resulting in insufficient anti-corrosion performance and an inability to meet the long-term anti-corrosion needs of high-end industrial fields.

Method used

The synergistic effect of modified nano-titanium dioxide, modified epoxy resin, zinc phosphate and aluminum tripolyphosphate is used to form a dense dual protection system of physical barrier and chemical passivation. Silica sol and metakaolin are combined to form an inorganic network structure. Through a refined preparation process, the uniform dispersion and stability of each component are ensured, and polydimethylsiloxane emulsion is used to reduce the surface tension of the coating.

Benefits of technology

The coating has achieved high corrosion resistance, durability and environmental protection. The coating exhibits excellent anti-corrosion performance in harsh environments and is suitable for high-temperature equipment and chemical pipelines, etc., which broadens the scope of application and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an inorganic copolymer anticorrosive paint and a preparation method thereof, and relates to the technical field of paints. The invention discloses inorganic copolymer anticorrosive paint. The coating is prepared from the following raw materials in parts by weight: 20 to 30 parts of silica sol, 8 to 15 parts of sodium hydroxide, 30 to 45 parts of metakaolin, 8 to 20 parts of quartz sand, 15 to 25 parts of water, 0.3 to 2 parts of sodium polyacrylate, 0.2 to 3 parts of polydimethylsiloxane emulsion, 5 to 12 parts of modified nano titanium dioxide, 6 to 10 parts of modified epoxy resin, 10 to 25 parts of hydroxyethyl methylacrylate, 5 to 10 parts of zinc phosphate, 3 to 8 parts of aluminum triphosphate and 2 to 6 parts of iron oxide red. The raw materials of the inorganic copolymer anticorrosive paint are scientifically proportioned, and the anticorrosive performance is enhanced through the modified nano titanium dioxide and the epoxy resin. Material uniformity is ensured through step-by-step feeding and ultrasonic dispersion in preparation, and stability is improved through vacuum defoaming and nitrogen protection. The components such as the silica sol and the zinc phosphate have a synergistic effect to form a compact coating, and the coating is high in corrosion resistance, good in constructability and suitable for various scenes.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of coating technology, in particular to an inorganic copolymer anticorrosive coating and a preparation method thereof. BACKGROUND

[0002] In the industrial field, metal materials are widely used in construction, shipbuilding, chemical equipment and other scenes due to their excellent mechanical properties, but metal corrosion is always the key factor restricting their service life. According to statistics, the economic loss caused by metal corrosion accounts for 2%-4% of the global GDP every year, and the equipment failure caused by corrosion can also lead to safety accidents and environmental pollution.

[0003] Traditional anticorrosive coatings are mostly based on organic polymers, which have certain corrosion resistance, but have poor temperature resistance and are prone to aging, and their service life is greatly shortened in harsh environments such as high temperature, high humidity, strong acid and alkali. Inorganic coatings have gradually attracted attention due to their advantages of high temperature resistance, chemical corrosion resistance, environmental protection and no volatilization, but existing inorganic coatings generally have poor film forming property, insufficient flexibility and easy cracking, which limits their application range.

[0004] Most of the inorganic anticorrosive coatings on the market rely on a single inorganic binder such as silica sol and phosphate, and the coating density is insufficient, and water vapor and corrosive media can easily penetrate. At the same time, the compatibility of inorganic fillers and binders is poor, and problems such as uneven dispersion and sedimentation easily occur, resulting in unstable coating performance. In addition, the existing preparation process lacks sufficient control of raw material pretreatment and dispersion process, which makes it difficult to ensure that the components of the coating fully react, affecting the crosslinking density and corrosion resistance of the coating.

[0005] With the increasing strictness of environmental protection requirements and the complexity of industrial environment, it is urgent to develop a new type of inorganic anticorrosive coating with excellent corrosion resistance, environmental friendliness and stable construction, to solve the shortcomings of traditional coatings in corrosion resistance, durability and environmental protection, and meet the needs of long-term corrosion protection in high-end industrial fields. SUMMARY

[0006] In view of the shortcomings of the prior art, the present application provides an inorganic copolymer anticorrosive coating and a preparation method thereof, which solves the problems of poor temperature resistance, easy aging and cracking, easy medium penetration, uneven dispersion and instability of traditional coatings.

[0007] To achieve the above purpose, the present application realizes the following technical solutions:

[0008] An inorganic copolymer anticorrosive coating, comprising the following raw materials by weight: 20-30 parts of silica sol, 8-15 parts of sodium hydroxide, 30-45 parts of metakaolin, 8-20 parts of quartz sand, 15-25 parts of water, 0.3-2 parts of sodium polyacrylate, 0.2-3 parts of dimethicone emulsion, 5-12 parts of modified nanometer titanium dioxide, 6-10 parts of modified epoxy resin, 10-25 parts of hydroxyethyl methacrylate, 5-10 parts of zinc phosphate, 3-8 parts of aluminum tripolyphosphate, and 2-6 parts of red iron oxide.

[0009] Further, the silica sol has a solid content of 25%-35%, ensures the bonding strength, and has a pH value of 9-10, providing a suitable alkaline environment for inorganic reaction; the quartz sand has a particle size of 40-80 mesh, and is calcined at 800-1000℃ for 2-3h before cooling for standby, removes impurities and moisture by calcination, improves hardness and is easy to disperse, and enhances the wear resistance and density of the coating; the sodium hydroxide is of analytical purity, with a purity of ≥96%, avoids impurity interference, ensures the stability of the system pH, and ensures the uniform formation of the inorganic network.

[0010] Further, the modified nanometer titanium dioxide has the following specific preparation steps:

[0011] A1, nanometer titanium dioxide is added to anhydrous ethanol, and ultrasonic dispersion is carried out at 300-400W for 30-40min to make the nanometer titanium dioxide uniformly suspended; then silane coupling agent KH-550 is added, and the temperature is raised to 80-90℃, and stirring is carried out at 200-300r / min for 4-6h; after the reaction is completed, the mixture is centrifuged at 3000-4000r / min for 15-20min, the precipitate is washed with anhydrous ethanol for 3-4 times, and dried at 60-70℃ for 8-10h to obtain the first modified product;

[0012] The alkoxy group in the silane coupling agent KH-550 molecule reacts with the hydroxyl group on the surface of the nanometer titanium dioxide to form a stable Si-O-Ti chemical bond, and introduces an organic amine group onto the surface of the nanometer particles. This process breaks the agglomeration tendency of nanometer titanium dioxide, and at the same time improves its interface compatibility with subsequent organic binders through organic groups, laying a foundation for subsequent compounding.

[0013] A2, take the first modified product into toluene, 250-350W power ultrasonic dispersion 20-30min, then add maleic anhydride, benzoyl peroxide, 110-120℃ reflux reaction 6-8h; after the reaction is completed, the product is transferred to a separatory funnel, washed with a mixture of toluene and ethanol with a volume ratio of 3:1 for 3-5 times, and then dried at 80-90℃ for 8-10h, add dichloromethane to the dried product, ultrasonic dispersion 10-15min, then add nano montmorillonite, 50-60℃ under 300-400r / min stirring reaction 3-4h, filter and wash the residue with dichloromethane, 80-90℃ drying 2-4h, to obtain the secondary modified product;

[0014] Under the initiation of benzoyl peroxide, maleic anhydride reacts with the amine group introduced in the first step to form polar groups containing carboxyl groups, further enhancing the chemical binding force of nanoparticles and resin; the subsequently added nano montmorillonite is combined with nano titanium dioxide through interlayer force, and the lamellar structure of montmorillonite constructs a physical barrier network, which can delay the penetration path of corrosion media such as water and chloride ions, and at the same time improve the dispersion stability of nanoparticles in the system.

[0015] A3, take the secondary modified product and disperse it in dimethylformamide, 200-300W ultrasonic treatment 15-20min, add polyvinylpyrrolidone, stir at 200-300r / min at 30-40℃ for 6-8h; after the reaction is completed, add 10% sodium silicate aqueous solution dropwise, continue to stir for 2-3h, then add hollow glass microbeads with a particle size of 20μm, stir uniformly, then wash the product with a mixture of dimethylformamide and water with a volume ratio of 4:1, and dry at 50-60℃ for 6-8h to obtain modified nano titanium dioxide.

[0016] Polyvinylpyrrolidone forms steric hindrance on the surface of nanoparticles through adsorption, preventing sedimentation and agglomeration during storage; the siloxane bond provided by the sodium silicate aqueous solution reacts with the surface of nano titanium dioxide and inorganic ingredients such as silica sol, enhancing the continuity of the inorganic network; 20μm hollow glass microbeads fill the pores of the coating, reducing defects and increasing the physical barrier effect, ultimately achieving the synergistic improvement of nanoparticle "compatibility-dispersibility-barrier".

[0017] Further, the amount ratio of nano titanium dioxide, anhydrous ethanol and silane coupling agent KH-550 is 500-600g:800-1000mL:30-40mL.

[0018] Further, the first modified product in A2, toluene, maleic anhydride, benzoyl peroxide, dichloromethane, nano-montmorillonite are used in a ratio of 200-300g: 500-700mL: 20-30g: 10-15g: 150-250mL: 5-10g.

[0019] Further, the second modified product in A3, dimethylformamide, polyvinylpyrrolidone, sodium silicate aqueous solution, hollow glass microspheres are used in a ratio of 150-250g: 400-600mL: 15-25g: 50-80mL: 10-15g.

[0020] Further, the modified epoxy resin, the specific preparation steps are as follows:

[0021] B1, dissolve the epoxy resin in ethylene glycol monobutyl ether, 200-300r / min stirring until dissolved, add polyetheramine D230, heat to 50-60℃ for 3-5h; after the reaction is completed, pour the mixed solution into a rotary evaporator, and remove the ethylene glycol monobutyl ether under the conditions of 60-70℃ and vacuum degree of 0.05-0.07MPa, to obtain a preliminary modified epoxy resin;

[0022] The amino group of polyetheramine D230 reacts with the epoxy group of the epoxy resin to introduce flexible polyether segments into the molecular chain of the epoxy resin. This process reduces the brittleness of the epoxy resin and relieves stress concentration through the deformation of the flexible segments, providing a basis for the flexibility of the coating.

[0023] B2, cool the preliminary modified epoxy resin to 30-40℃, add the multi-walled carbon nanotubes treated by surface acidification, and ultrasonically disperse for 30-40min at 350-450W, then stir at 300-400r / min at 60-70℃ for 4-6h; after the reaction is completed, add nano-silica aerogel and continue to stir for 2-3h to make it uniformly dispersed, to obtain a second modified epoxy resin;

[0024] The multi-walled carbon nanotubes treated by concentrated nitric acid-concentrated sulfuric acid mixed acid have carboxyl and hydroxyl groups introduced on their surface, which can react with the hydroxyl and epoxy groups of the epoxy resin to achieve "molecular level combination"; the one-dimensional nanostructure of the carbon nanotubes constructs a three-dimensional reinforcing network, significantly improving the tensile strength and impact resistance of the resin; the subsequently added nano-silica aerogel can adsorb corrosion media and reduce thermal conductivity due to its high specific surface area and porous structure, while filling the gaps between the resins to enhance the compactness of the coating.

[0025] B3, glycidyl methacrylate, azobisisobutyronitrile are added into the system after the second modification, nitrogen is introduced to replace air, the nitrogen flow is kept at 50-80 mL / min, the reaction device is heated to 80-90℃, and the reaction is carried out for 5-7 h; after the reaction is completed, the temperature is cooled to room temperature, and the hydroxyl-terminated hyperbranched polyester is added, and the reaction is carried out at 40-50℃ with stirring at 200-300 r / min for 3-4 h to obtain the final modified epoxy resin.

[0026] Glycidyl methacrylate is polymerized with epoxy resin segments under the initiation of azobisisobutyronitrile, more epoxy groups are introduced, the density of crosslinking sites is increased, and a more compact three-dimensional network structure is formed after nitrogen protection reaction; the multiple hydroxyl groups of the hydroxyl-terminated hyperbranched polyester react with the epoxy groups, the branching degree of the molecular chain is increased, the stress is further dispersed, and the adhesion of the coating to the substrate is improved, and finally the synergistic optimization of the flexibility, mechanical strength and corrosion resistance of the epoxy resin is realized.

[0027] Further, the amount ratio of the epoxy resin, ethylene glycol monobutyl ether and polyetheramine D230 in B1 is 400-500 g:600-800 mL:30-40 g.

[0028] Further, the amount ratio of the surface acid-treated multi-walled carbon nanotubes and nano-silica aerogel in B2 is 20-30 g:10-15 g.

[0029] Further, the amount ratio of glycidyl methacrylate, azobisisobutyronitrile and hydroxyl-terminated hyperbranched polyester in B3 is 15-25 g:5-10 g:20-30 g.

[0030] Further, the surface acid-treated multi-walled carbon nanotubes in B2 are acid-treated by the following method: the multi-walled carbon nanotubes are added to a mixture of concentrated nitric acid and concentrated sulfuric acid with a volume ratio of 1:3, stirred at 70℃ for 4 h, then filtered, washed with water until neutral, and dried. The synergistic effect of concentrated nitric acid and concentrated sulfuric acid efficiently introduces active groups such as carboxyl and hydroxyl groups on the surface of the carbon nanotubes, significantly improves the compatibility and interfacial bonding force with the epoxy resin, and enhances the mechanical properties of the coating.

[0031] A preparation method of an inorganic copolymer anticorrosion coating, specifically comprising the following steps:

[0032] S1, 20-30 parts of silica sol are injected into a stirred tank, then 8-15 parts of sodium hydroxide and 15-25 parts of water are added, the stirring speed is set to 600-800 r / min, and the mixture is continuously stirred for 20-30 h to ensure that there is no precipitation and stratification, and a uniform premixed solution is obtained; ensure that the silica sol and sodium hydroxide are fully reacted to form a uniform inorganic precursor solution, which lays a foundation for subsequent network structure construction;

[0033] S2, transfer the premixed solution to a high-speed mixer, turn on the stirring device, set the speed to 500-600 r / min, add 30-45 parts of metakaolin in two portions, stir for 5-10 min after each addition before adding the next portion, and continue stirring for 30-40 min after all the metakaolin is added; stepwise addition and stirring avoid metakaolin agglomeration and ensure uniform dispersion of metakaolin in the premixed solution, improving the uniformity and compactness of the inorganic network structure;

[0034] S3, keep the stirring device speed at 400-500 r / min, add 5-12 parts of modified nano titanium dioxide, stir for 15-20 min; then add 6-10 parts of modified epoxy resin, continue stirring for 20-25 min; then add 10-25 parts of hydroxyethyl methacrylate, stir for 10-15 min; then add 5-10 parts of zinc phosphate, 3-8 parts of aluminum tripolyphosphate, and 2-6 parts of iron oxide red, respectively, and stir for 10-12 min after each addition; then add 8-20 parts of quartz sand, stir for 20-25 min; finally add 0.3-2 parts of sodium polyacrylate and 0.2-3 parts of polydimethylsiloxane emulsion, and continue stirring for 1-2 h; before adding each raw material, make sure that the previous raw material has been completely dispersed to avoid agglomeration; variable speed stirring is adapted to the characteristics of different raw materials to ensure uniform dispersion of nanoparticles, fillers and additives, and avoid performance fluctuations caused by agglomeration; stepwise confirmation of dispersion state ensures full mixing of components and improves paint storage stability;

[0035] S4, after stirring, let the material stand for 5-10 min, filter the material using a 200-300 mesh filter screen, slowly push the material with a scraper during the filtering process to ensure complete filtration, and the filtered paint needs to be vacuum degassed, the degassing pressure is -0.08 to -0.09 MPa, and the degassing time is 15-20 min, obtaining an inorganic copolymer anticorrosive coating; filtering removes large particle impurities to ensure paint fineness and leveling; vacuum degassing eliminates internal air bubbles to avoid defects such as pinholes and shrinkage holes after film formation.

[0036] Further, the standing process in S4 needs to be carried out in a sealed stirring kettle, and nitrogen is introduced during the standing process to avoid excessive contact of the material with air, maintain the chemical stability of the paint, prolong the storage period, and ensure the consistency of the construction performance.

[0037] The present application provides an inorganic copolymer anticorrosive coating and a preparation method, which has the following beneficial effects:

[0038] 1、The present application forms a dense physical barrier and chemical passivation double protection system in the coating interior through the synergistic effect of modified nano-titanium dioxide, modified epoxy resin and zinc phosphate, aluminum tripolyphosphate. The modified nano-titanium dioxide is modified by silane coupling agent, maleic anhydride and the like, and the compatibility with the base material is greatly improved, which can uniformly fill the coating pores and prevent the penetration of corrosive media such as water vapor and chloride ions; the zinc phosphate and aluminum tripolyphosphate form a passivation film on the metal surface to inhibit the electrochemical corrosion reaction; and the organic-inorganic interpenetrating network structure formed by the modified epoxy resin and silica sol further enhances the adhesion of the coating to the substrate, effectively resists corrosion and erosion in harsh environments such as long-term immersion and dry-wet alternating environments, and greatly prolongs the service life of the coating.

[0039] 2、The scientific ratio of inorganic components and organic components in the coating system realizes the balance of mechanical properties. The silica sol and metakaolin form a rigid inorganic network structure during the reaction process, which gives the coating excellent hardness and high temperature resistance; the modified epoxy resin is modified by multi-walled carbon nanotubes and hydroxyl-terminated hyperbranched polyester, and the flexibility of its molecular chain is enhanced, which can effectively alleviate the stress concentration of the coating under cold and hot cycles and mechanical impact, and avoid the defect that traditional inorganic coatings are prone to cracking; the introduction of polydimethylsiloxane emulsion reduces the surface friction coefficient of the coating, improves the wear resistance and impact resistance, so that the coating can not only withstand mechanical wear in industrial environments, but also adapt to the micro-deformation of the substrate, reducing the peeling of the coating caused by the expansion of the substrate.

[0040] 3、Through the synergistic effect of fine preparation process and additives, the stability of the coating is ensured during storage, construction and film formation. In the preparation process, stepwise feeding is combined with ultrasonic dispersion and high-speed stirring to uniformly disperse the modified nano-titanium dioxide, quartz sand and other solid particles, avoiding agglomeration; polyacrylic acid sodium as a dispersant can effectively prevent the settling of raw materials and prolong the storage period; vacuum degassing and nitrogen protection process reduces the internal bubbles of the coating, and the film is more uniform during construction, without defects such as pinholes and shrinkage; polydimethylsiloxane emulsion reduces the surface tension of the coating and improves the leveling property, so that the coating can form a continuous and complete coating film on various substrates such as metal and concrete, ensuring the consistency and reliability of the coating performance after construction.

[0041] 4、The coating is mainly composed of inorganic components, supplemented by low-toxicity and high-efficiency organic additives, which greatly reduces VOC emissions and meets environmental protection requirements. At the same time, due to the effect of inorganic network structure and modified components, the coating has excellent high temperature resistance and chemical corrosion resistance: the inorganic framework formed by silica sol and metakaolin can withstand high temperatures without decomposition, and the modified epoxy resin improves the resistance to acid and alkali medium corrosion, making it suitable for use in high temperature equipment, chemical pipelines, marine engineering and other harsh environments. In addition, there is no stratification or precipitation during the storage of the coating, and the coating has strong adaptability to environmental temperature and humidity during construction, which can meet the coating needs in different working conditions, significantly widening the application range of the anticorrosive coating. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the protection scope of the present application.

[0043] Embodiment 1, preparation of inorganic copolymer anticorrosive paint, the specific preparation steps are as follows:

[0044] S1, 20 parts of silica sol were injected into a stirred tank, then 8 parts of sodium hydroxide and 15 parts of water were added, the stirring speed was set to 600 r / min, and the mixture was continuously stirred for 20 h to ensure that there was no precipitation and stratification, and a uniform premixed solution was obtained;

[0045] S2, the premixed solution was transferred to a high-speed stirrer, the stirring device was turned on, the stirring speed was set to 500 r / min, 30 parts of metakaolin was added in two portions, and after each addition, the mixture was stirred for 5 min before the next addition, and after all the additions were completed, the mixture was continuously stirred for 30 min;

[0046] S3, the stirring speed was kept at 400 r / min, 6 parts of epoxy resin was added, and the mixture was stirred for 20 min; then 10 parts of hydroxyethyl methacrylate was added, and the mixture was stirred for 10 min; then 5 parts of zinc phosphate, 3 parts of aluminum tripolyphosphate, and 2 parts of red iron oxide were added in sequence, and each material was stirred for 10 min; then 8 parts of quartz sand was added, and the mixture was stirred for 20 min; finally, 0.3 parts of sodium polyacrylate and 0.2 parts of polydimethylsiloxane emulsion were added, and the mixture was continuously stirred for 1 h, and before adding each material, it was necessary to confirm that the previous material had been completely dispersed to avoid agglomeration;

[0047] S4, after the stirring was completed, the material was allowed to stand for 5 min, and then filtered using a 200-mesh filter screen, and during the filtering process, the material was slowly pushed using a scraper to ensure that the filtering was sufficient, and the filtered paint was subjected to vacuum degassing treatment, the degassing pressure was-0.08 MPa, and the degassing time was 15 min, and an inorganic copolymer anticorrosive paint was obtained.

[0048] Embodiment 2, preparation of inorganic copolymer anticorrosive paint, the specific preparation steps are as follows:

[0049] S1, 30 parts of silica sol were injected into a stirred tank, then 15 parts of sodium hydroxide and 25 parts of water were added, the stirring speed was set to 800 r / min, and the mixture was continuously stirred for 30 h to ensure that there was no precipitation and stratification, and a uniform premixed solution was obtained;

[0050] S2, the premixed solution is transferred to a high-speed mixer, the stirring device is turned on, the rotating speed is set to 600 r / min, 45 parts of metakaolin are added in two portions, after each addition, the material is stirred for 10 min before the next addition, after all the material is added, the stirring is continued for 40 min;

[0051] S3, the rotating speed of the stirring device is kept at 500 r / min, 10 parts of epoxy resin are added, and stirred for 25 min; then 25 parts of hydroxyethyl methacrylate are added, and stirred for 15 min; then 10 parts of zinc phosphate, 8 parts of aluminum tripolyphosphate, and 6 parts of red iron oxide are added in sequence, and stirred for 12 min after each addition; then 20 parts of quartz sand are added, and stirred for 25 min; finally, 2 parts of sodium polyacrylate and 3 parts of dimethyl silicone emulsion are added, and the stirring is continued for 2 h, and before each addition of raw material, it is necessary to confirm that the previous raw material has been completely dispersed to avoid agglomeration;

[0052] S4, after the stirring is completed, the material is left to stand for 10 min, a 300-mesh filter screen is used to filter the material, a scraper is used to slowly push the material during the filtering process to ensure that the filtering is sufficient, and the filtered coating needs to be subjected to vacuum degassing treatment, the degassing pressure is -0.09 MPa, and the degassing time is 20 min, and an inorganic copolymer anticorrosive coating is obtained.

[0053] Example 3, an inorganic copolymer anticorrosive coating is prepared, and the specific preparation steps are as follows:

[0054] S1, 25 parts of silica sol are injected into a stirring kettle, then 11 parts of sodium hydroxide and 20 parts of water are added, the stirring rotating speed is set to 700 r / min, and the stirring and mixing are continued for 25 h to ensure that there is no precipitation and stratification, and a uniform premixed solution is obtained;

[0055] S2, the premixed solution is transferred to a high-speed mixer, the stirring device is turned on, the rotating speed is set to 550 r / min, 38 parts of metakaolin are added in two portions, after each addition, the material is stirred for 7 min before the next addition, after all the material is added, the stirring is continued for 35 min;

[0056] S3, the rotating speed of the stirring device is kept at 450 r / min, 8 parts of epoxy resin are added, and stirred for 22 min; then 17 parts of hydroxyethyl methacrylate are added, and stirred for 12 min; then 7 parts of zinc phosphate, 5 parts of aluminum tripolyphosphate, and 4 parts of red iron oxide are added in sequence, and stirred for 11 min after each addition; then 14 parts of quartz sand are added, and stirred for 22 min; finally, 1 part of sodium polyacrylate and 1 part of dimethyl silicone emulsion are added, and the stirring is continued for 1.5 h, and before each addition of raw material, it is necessary to confirm that the previous raw material has been completely dispersed to avoid agglomeration;

[0057] S4, after the stirring, the material was allowed to stand for 7 min, and the material was filtered using a 250-mesh filter screen, the material was slowly pushed by a scraper during the filtering process to ensure sufficient filtering, and the filtered coating was subjected to vacuum degassing treatment, the degassing pressure was -0.08 MPa, and the degassing time was 17 min, thereby obtaining the inorganic copolymer anticorrosive coating.

[0058] Example 4, preparation of modified nano-titanium dioxide, the specific preparation steps are as follows:

[0059] A1, 500 g of nano-titanium dioxide was added to 800 mL of anhydrous ethanol, and ultrasonic dispersion was performed at 300 W for 30 min to uniformly suspend the nano-titanium dioxide; then 30 mL of silane coupling agent KH-550 was added, and the temperature was raised to 80 °C, and stirring was performed at 200 r / min for 4 h; after the reaction was completed, the mixture was centrifuged at 3000 r / min for 15 min, the precipitate was washed with anhydrous ethanol for 3 times, and drying was performed at 60 °C for 8 h, thereby obtaining the first modified product;

[0060] A2, 200 g of the first modified product was added to 500 mL of toluene, ultrasonic dispersion was performed at 250 W for 20 min, then 20 g of maleic anhydride and 10 g of benzoyl peroxide were added, and reflux reaction was performed at 110 °C for 6 h; after the reaction was completed, the product was transferred to a separatory funnel, washed with a mixed solution of toluene and ethanol with a volume ratio of 3:1 for 3 times, and then dried at 80 °C for 8 h; 150 mL of dichloromethane was added to the dried product, ultrasonic dispersion was performed for 10 min, then 5 g of nano-montmorillonite was added, and stirring reaction was performed at 50 °C and at 300 r / min for 3 h; the product was filtered and the filter residue was washed with dichloromethane, and then dried at 80 °C for 2 h, thereby obtaining the second modified product;

[0061] A3, 150 g of the second modified product was dispersed in 400 mL of dimethylformamide, and ultrasonic treatment was performed at 200 W for 15 min; 15 g of polyvinylpyrrolidone was added, and stirring reaction was performed at 30 °C and at 200 r / min for 6 h; after the reaction was completed, 50 mL of a 10% sodium silicate aqueous solution was added dropwise, and stirring was continued for 2 h; then 10 g of hollow glass microbeads with a particle size of 20 μm was added, the product was stirred uniformly, and then a mixed solution of dimethylformamide and water with a volume ratio of 4:1 was used to wash the product; drying was performed at 50 °C for 6 h, thereby obtaining the modified nano-titanium dioxide.

[0062] Example 5, preparation of modified nano-titanium dioxide, the specific preparation steps are as follows:

[0063] A1, 600 g of nano-titanium dioxide was added into 1000 mL of anhydrous ethanol, and dispersed by ultrasonic at 400 W for 30-40 min to make the nano-titanium dioxide uniformly suspended; then 40 mL of silane coupling agent KH-550 was added, and the mixture was stirred at 300 r / min and reacted at 90°C for 6 h; after the reaction was completed, the mixture was centrifuged at 4000 r / min for 20 min, the precipitate was washed with anhydrous ethanol for 4 times, and dried at 70°C for 10 h to obtain the first modified product;

[0064] A2, 300 g of the first modified product was added into 700 mL of toluene, and dispersed by ultrasonic at 350 W for 30 min, then 30 g of maleic anhydride and 15 g of benzoyl peroxide were added, and the mixture was refluxed at 120°C for 8 h; after the reaction was completed, the product was transferred to a separatory funnel, washed with a mixture of toluene and ethanol (volume ratio 3:1) for 5 times, and then dried at 90°C for 10 h; 250 mL of dichloromethane was added into the dried product, and dispersed by ultrasonic for 15 min, then 10 g of nano-montmorillonite was added, and the mixture was stirred at 400 r / min and reacted at 60°C for 4 h; the mixture was filtered, the residue was washed with dichloromethane, and dried at 90°C for 4 h to obtain the second modified product;

[0065] A3, 250 g of the second modified product was dispersed in 600 mL of dimethylformamide, and treated by ultrasonic at 300 W for 20 min, then 25 g of polyvinylpyrrolidone was added, and the mixture was stirred at 300 r / min and reacted at 40°C for 8 h; after the reaction was completed, 80 mL of 10% sodium silicate aqueous solution was added dropwise, and the mixture was stirred for another 3 h; then 15 g of hollow glass microspheres with a particle size of 20 μm was added, and the mixture was stirred uniformly, and then washed with a mixture of dimethylformamide and water (volume ratio 4:1); the product was dried at 60°C for 8 h to obtain the modified nano-titanium dioxide.

[0066] Example 6, preparation of modified epoxy resin, the specific preparation steps are as follows:

[0067] B1, 400 g of epoxy resin was dissolved in 600 mL of ethylene glycol monobutyl ether, and stirred at 200 r / min until dissolved; then 30 g of polyetheramine D230 was added, and the mixture was heated to 50°C and reacted for 3 h; after the reaction was completed, the mixture was poured into a rotary evaporator, and the ethylene glycol monobutyl ether was removed by rotary evaporation at 60°C and a vacuum degree of 0.05 MPa to obtain a preliminary modified epoxy resin;

[0068] B2, the preliminary modified epoxy resin was cooled to 30°C, and 20 g of multi-walled carbon nanotubes treated by surface acidification was added; the mixture was dispersed by ultrasonic at 350 W for 30 min, and then stirred at 300 r / min and reacted at 60°C for 4 h; after the reaction was completed, 10 g of nano-silica aerogel was added, and the mixture was stirred for another 2 h to make the nano-silica aerogel uniformly dispersed, and a second modified epoxy resin was obtained;

[0069] B3, to the second modified system, add 15 g of glycidyl methacrylate, 5 g of azobisisobutyronitrile, replace air with nitrogen, keep nitrogen flow at 50 mL / min, heat the reaction device to 80℃, react for 5 h; after the reaction is completed, cool to room temperature, add 20 g of hydroxyl-terminated hyperbranched polyester, stir at 200 r / min at 40℃ for 3 h, to obtain the final modified epoxy resin.

[0070] Example 7, preparation of modified epoxy resin, the specific preparation steps are as follows:

[0071] B1, dissolve 500 g of epoxy resin in 800 mL of ethylene glycol monobutyl ether, stir at 300 r / min until dissolved, add 40 g of polyetheramine D230, heat to 60℃ and react for 5 h; after the reaction is completed, pour the mixture into a rotary evaporator, remove the ethylene glycol monobutyl ether at 70℃ under a vacuum degree of 0.07 MPa, to obtain a preliminary modified epoxy resin;

[0072] B2, cool the preliminary modified epoxy resin to 40℃, add 30 g of multi-walled carbon nanotubes treated by surface acidification, ultrasonically disperse at 450 W for 40 min, then stir at 400 r / min at 70℃ for 6 h; after the reaction is completed, add 15 g of nano-silica aerogel, continue to stir for 3 h to make it uniformly dispersed, to obtain a second modified epoxy resin;

[0073] B3, to the second modified system, add 25 g of glycidyl methacrylate, 10 g of azobisisobutyronitrile, replace air with nitrogen, keep nitrogen flow at 80 mL / min, heat the reaction device to 90℃, react for 7 h; after the reaction is completed, cool to room temperature, add 30 g of hydroxyl-terminated hyperbranched polyester, stir at 300 r / min at 50℃ for 4 h, to obtain the final modified epoxy resin.

[0074] Comparative Example 1, preparation of inorganic copolymer anticorrosive coating, the specific preparation steps are as follows:

[0075] The remaining steps are unchanged, only 8 parts of the modified nano-titanium dioxide prepared in Example 4 is first added to S3 of Example 3, stir for 17 min, then continue the subsequent operation, to obtain the inorganic copolymer anticorrosive coating.

[0076] Comparative Example 2, preparation of inorganic copolymer anticorrosive coating, the specific preparation steps are as follows:

[0077] The remaining steps are unchanged, only the epoxy resin of Example 3 is replaced with the modified epoxy resin prepared in Example 7, to obtain the inorganic copolymer anticorrosive coating.

[0078] Comparative Example 3, preparation of inorganic copolymer anticorrosive coating, the specific preparation steps are as follows:

[0079] The remaining steps are unchanged, and 8 parts of the modified nano-titanium dioxide prepared in Example 4 are first added to S3 of Example 3, stirring for 17 min, then the epoxy resin is replaced with the modified epoxy resin prepared in Example 7 and the subsequent operation is continued, to prepare an inorganic copolymer anticorrosive coating.

[0080] Performance test

[0081] Test item Test standard / method Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Resistance to neutral salt spray GB / T 1771-2007 Rust grade Ri 4 Rust grade Ri 3 Rust grade Ri 3 Rust grade Ri 2 Rust grade Ri 1 Rust grade Ri 0 Adhesion (crosshatch method) GB / T 9286-2021 Level 3 Level 3 Level 2 Level 2 Level 1 Level 0 Pencil hardness GB / T 6739-2022 H H 2H 2H 2H 3H Resistance to heat (constant temperature oven continuous test for 1000 h) GB / T 1735-2009 After 150℃ test, coating surface yellowing, level 3, adhesion decreased to level 4 After 150℃ test, coating slightly yellowing, level 2, adhesion decreased to level 3 After 180℃ test, coating slightly yellowing, level 2, adhesion had no obvious change, still level 2 After 200℃ test, coating no yellowing, level 1, adhesion had no obvious change, still level 2 After 200℃ test, coating no yellowing, level 1, adhesion had no obvious change, still level 1 After 250℃ test, coating no yellowing, level 0, adhesion had no obvious change, still level 0 Acid resistance (5% H2SO4, 72 h) GB / T 9274-1988 Weight loss 5.2% Weight loss 4.8% Weight loss 4.5% Weight loss 1.8% Weight loss 2.2% Weight loss 0.5% Storage stability (3 months) Standing observation whether delamination / precipitation Slight delamination Slight precipitation A small amount of precipitation No delamination / precipitation No delamination / precipitation No delamination / precipitation

[0082] According to the performance test results, the inorganic copolymer anticorrosive coatings of the examples and the comparative examples show obvious differences in many performances: in terms of neutral salt spray resistance, the rust grade Ri0 of the comparative example 3 with the addition of modified nano-titanium dioxide and modified epoxy resin is far superior to that of the examples 1-3 and the comparative examples 1-2 with the addition of a single modified component; in terms of adhesion, the comparative example 3 reaches 0 level, which is the best, the examples 1-2 are 3 levels, and the comparative example 2 is 1 level; in terms of pencil hardness, the comparative example 3 reaches 3H, the examples 1-2 are H, and the others are 2H; in terms of heat resistance, the comparative examples 1-3 can withstand 200-250℃ without change, which is superior to the yellowing phenomenon of 150-180℃ of the examples 1-3; in terms of acid resistance, the weight loss rate of the comparative example 3 is only 0.5%, which is significantly lower than the 4.5%-5.2% of the examples and the 1.8%-2.2% of the comparative examples 1-2; in terms of storage stability, the comparative examples 1-3 have no stratification / precipitation, and the examples 1-3 have slight stratification or precipitation. Overall, the comparative example 3 with the addition of modified nano-titanium dioxide and modified epoxy resin performs best in various performances, highlighting the significant improvement in the comprehensive performance of the coating due to the synergistic effect of the two modified components.

[0083] The above is only an example and description of the present application, and those skilled in the art can make various modifications or supplements to the described specific examples or use similar ways to replace them, as long as they do not deviate from the invention or exceed the scope defined by the present claims, which shall fall within the protection scope of the present application.

Claims

1. An inorganic copolymer anticorrosive coating, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of silica sol, 8-15 parts of sodium hydroxide, 30-45 parts of metakaolin, 8-20 parts of quartz sand, 15-25 parts of water, 0.3-2 parts of sodium polyacrylate, 0.2-3 parts of polydimethylsiloxane emulsion, 5-12 parts of modified nano titanium dioxide, 6-10 parts of modified epoxy resin, 10-25 parts of hydroxyethyl methacrylate, 5-10 parts of zinc phosphate, 3-8 parts of aluminum tripolyphosphate, and 2-6 parts of red iron oxide.

2. The inorganic copolymer anticorrosive coating according to claim 1, characterized in that: The solid content of the silica sol is 25%-35%, and the pH value is 9-10; the particle size of the quartz sand is 40-80 mesh, and it is calcined at 800-1000° C. for 2-3 hours and then cooled for standby use; the sodium hydroxide is of analytical grade with a purity of ≥96%.

3. The inorganic copolymer anticorrosive coating according to claim 1, characterized in that: The modified nano titanium dioxide is specifically prepared in the following steps: A1. Add nano-titanium dioxide to anhydrous ethanol and perform ultrasonic dispersion at 300-400W for 30-40 minutes to uniformly suspend the nano-titanium dioxide; then add silane coupling agent KH-550, raise the temperature to 80-90°C, and stir at 200-300r / min for 4-6 hours; after the reaction, centrifuge the mixture at 3000-4000r / min for 15-20 minutes, wash the precipitate with anhydrous ethanol 3-4 times, and dry at 60-70°C for 8-10 hours to obtain the first modified product; A2. The first modified product was added to toluene and ultrasonically dispersed at 250-350W power for 20-30 minutes. Maleic anhydride and benzoyl peroxide were then added, and the mixture was refluxed at 110-120°C for 6-8 hours. After the reaction was completed, the product was transferred to a separatory funnel and washed 3-5 times with a mixed solution of toluene and ethanol in a volume ratio of 3:

1. The product was then dried at 80-90°C for 8-10 hours. Dichloromethane was added to the dried product, and ultrasonically dispersed for 10-15 minutes. Nano-montmorillonite was then added, and the mixture was stirred at 300-400 r / min at 50-60°C for 3-4 hours. The residue was filtered and washed with dichloromethane, and then dried at 80-90°C for 2-4 hours to obtain a second modified product. A3. Disperse the secondary modified product in dimethylformamide, perform ultrasonic treatment at 200-300W for 15-20min, add polyvinylpyrrolidone, and stir at 200-300r / min at 30-40℃ for 6-8h. After the reaction, add a 10% sodium silicate aqueous solution by mass fraction, continue stirring for 2-3h, then add hollow glass microspheres with a particle size of 20μm, stir evenly, and then wash the product with a mixed solution of dimethylformamide and water with a volume ratio of 4:

1. Dry at 50-60℃ for 6-8h to obtain modified nano-titanium dioxide.

4. The inorganic copolymer anticorrosive coating according to claim 3, characterized in that: The dosage ratio of the nano titanium dioxide, anhydrous ethanol, and silane coupling agent KH-550 is 500-600 g: 800-1000 mL: 30-40 mL; The usage ratio of the first modified product, toluene, maleic anhydride, benzoyl peroxide, dichloromethane, and nano-montmorillonite in A2 is 200-300 g: 500-700 mL: 20-30 g: 10-15 g: 150-250 mL: 5-10 g; The usage ratio of the secondary modified product, dimethylformamide, polyvinyl pyrrolidone, sodium silicate aqueous solution, and hollow glass microspheres in A3 is 150-250 g: 400-600 mL: 15-25 g: 50-80 mL: 10-15 g.

5. The inorganic copolymer anticorrosive coating according to claim 1, characterized in that: The modified epoxy resin is specifically prepared in the following steps: B1, dissolving epoxy resin in ethylene glycol monobutyl ether, stirring at 200-300r / min until dissolved, adding polyetheramine D230, heating to 50-60°C and reacting for 3-5h; after the reaction is completed, pouring the mixed solution into a rotary evaporator, and removing ethylene glycol monobutyl ether by rotary evaporation at 60-70°C and a vacuum degree of 0.05-0.07MPa to obtain a preliminary modified epoxy resin; B2. Cool the preliminarily modified epoxy resin to 30-40°C, add surface-acidified multi-walled carbon nanotubes, and disperse them ultrasonically at 350-450W for 30-40 minutes. Then, stir at 300-400 rpm for 4-6 hours at 60-70°C. After the reaction, add nano-silica aerogel and continue stirring for 2-3 hours to uniformly disperse the nano-silica aerogel to obtain a second modified epoxy resin. B3. Add glycidyl methacrylate and azobisisobutyronitrile to the system after the second modification, introduce nitrogen to replace the air, maintain the nitrogen flow rate at 50-80 mL / min, heat the reaction apparatus to 80-90 ° C, and react for 5-7 hours; after the reaction is completed, cool to room temperature, add terminal hydroxyl hyperbranched polyester, and stir at 40-50 ° C at 200-300 r / min for 3-4 hours to obtain the final modified epoxy resin.

6. The inorganic copolymer anticorrosive coating according to claim 5, characterized in that: The usage ratio of epoxy resin, ethylene glycol monobutyl ether and polyetheramine D230 in B1 is 400-500g:600-800mL:30-40g; The ratio of the surface-acidified multi-walled carbon nanotubes and the nano-silica aerogel in B2 is 20-30 g: 10-15 g; The usage ratio of glycidyl methacrylate, azobisisobutyronitrile and terminal hydroxyl hyperbranched polyester in B3 is 15-25g: 5-10g: 20-30g.

7. The inorganic copolymer anticorrosive coating according to claim 5, characterized in that: The multi-walled carbon nanotubes in B2 that have undergone surface acidification treatment are treated by adding the multi-walled carbon nanotubes into a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3, stirring under reflux at 70° C. for 4 hours, then filtering, washing with water until neutral, and drying.

8. A method for preparing an inorganic copolymer anticorrosive coating, characterized in that: The specific steps include: S1. Pour 20-30 parts of silica sol into a stirring kettle, then add 8-15 parts of sodium hydroxide and 15-25 parts of water, set the stirring speed to 600-800 r / min, and continue stirring and mixing for 20-30 hours to ensure that there is no precipitation or stratification to obtain a uniform premixed solution; S2. Transfer the premixed solution to a high-speed blender, turn on the stirring device, set the speed to 500-600 r / min, add 30-45 parts of metakaolin in two times, stir for 5-10 minutes after each addition before adding the next material, and continue stirring for 30-40 minutes after all the additions are completed; S3, maintain the stirring equipment speed at 400-500r / min, add 5-12 parts of modified nano titanium dioxide, and stir for 15-20min; then add 6-10 parts of modified epoxy resin, continue stirring for 20-25min; then add 10-25 parts of hydroxyethyl methacrylate, and stir for 10-15min; then add 5-10 parts of zinc phosphate, 3-8 parts of aluminum tripolyphosphate, and 2-6 parts of red iron oxide in sequence, and stir for 10-12min after adding each raw material; then add 8-20 parts of quartz sand and stir for 20-25min; finally, add 0.3-2 parts of sodium polyacrylate and 0.2-3 parts of polydimethylsiloxane emulsion, and continue stirring for 1-2h. Before adding each raw material, confirm that the previous raw material has been completely dispersed to avoid agglomeration; S4. After stirring, let the material stand for 5-10 minutes, filter the material with a 200-300 mesh filter, and slowly push the material with a scraper during the filtration process to ensure sufficient filtration. The filtered coating needs to be vacuum degassed with a degassed pressure of -0.08 to -0.09 MPa and a degassed time of 15-20 minutes to obtain an inorganic copolymer anti-corrosion coating.

9. The method for preparing an inorganic copolymer anticorrosive coating according to claim 8, characterized in that: The standing process in S4 needs to be carried out in a closed stirred tank, and nitrogen protection is introduced during the standing process to avoid excessive contact between the material and air.

Citation Information

Patent Citations

  • Fluorine nanometer composite modified anticorrosion paint

    CN106398499A

  • Method for preparing amino functionalized carbon nanotube / epoxy resin compound material

    CN106433034A

  • Preparation method of anticorrosion epoxy resin embroidered coating containing coupled, dispersed and modified pigment fillings

    CN107779052A

  • High-toughness organic-inorganic composite marine anticorrosive paint and preparation method thereof

    CN111154299A

  • Inorganic polymer coating as well as preparation method and application thereof

    CN115537051A

Cited By

  • Ultraviolet-resistant antioxidant multi-layer composite drag reduction film and preparation method thereof

    CN121271437A